Morphometric analysis of Arun River Valley, eastern Nepal - Thakur, Pramod Kumar (Journal of Nepal Geological Society, 2003)
The Arun River shows antecedent characteristics but almost all tributaries show consequent characteristics. The drainage system of the Arun River Valley (ARV) is influenced by local geological structures in number of ways. The sharp bending, sudden high gradient, narrow valleys that suddenly become wide are common. In the ARV, major tributaries are of sixth order, as the order becomes higher, total number of stream segments becomes progressively smaller, but physical dimensions of the streams increase gradually. In some areas, the divides are low and indistinct, while in others they form high mountain systems. Valley deepening is affected by various factors such as- hydraulic action, corrosion/abrasion of the valley base and weathering of the stream bed increased by subsequent removal of weathered materials. Valley deepening is very high between Pisu la and the Barun Dovan; between the Num and Yamchung as well as Leguwaghat and Barachetra. Valley widening process is predominant near Kimathanka, between Tumlingtar and Surtibari and Sattare areas. The Arun River, flowing in the state of channel equilibrium condition partially modified after local recent tectonic events. In the near future there is very low risk of vast channel shifting phenomena in the valley. The paper describes major morphometrical analysis of the Arun River Valley, eastern Nepal.